Menyatukan Jarak, Bingkai Toleransi dalam Film Pendek dan Efektivitasnya sebagai Media Pembelajaran - Hidayat, Yasin; Mathoriyah, Lailatul; Ashoumi, Hilyah (JoEMS (Journal of Education and Management Studies), 2022)
This study aims: to instill the value of tolerance in students of SMAN Ploso by providing examples of the diversity that exists in the village of Distance through film media. This research is a research and development research. The data observed were data on religious diversity in the village of Distance which was then continued by observing the need for learning media on tolerance material at SMAN Ploso. The media effectiveness test was carried out by applying this film as a learning medium on Islamic education material with the pre-test and post-test models. The post test results show that the scores obtained by students in the experimental class using film media are higher than the post-test scores for the control class using student work overtime media. Attractive learning media is proven to be able to increase students' interest in tolerance material.